Analysis of intra-familial transmission of Helicobacter pylori in Japanese families. Issue 1 (January 2015) - Osaki, Takako; Konno, Mutsuko; Yonezawa, Hideo; Hojo, Fuhito; Zaman, Cynthia; Takahashi, Michiko; Fujiwara, Shinichi; Kamiya, Shigeru
Abstract : Intra-familial infection is considered to be one of the main routes of transmission for Helicobacter pylori in Japan. We assessed the genomic profiles of H. pylori isolates from family members by multi-locus sequence typing (MLST) and identified the original strain infecting the index child. A total of 19 isolates from five families were analysed by MLST using seven housekeeping genes and by random amplification of polymorphic DNA (RAPD)-PCR. Phylogenetic analysis was performed using nucleotide sequences of the seven loci. Two or more different types of H. pylori strains were indicated in three (K-1, K-2 and K-5) out of five families. Independent genotypes of H. pylori strains were detected from all members of the other two families suggesting that these strains (K26-28 and K29-33) may be dominant. Mother-to-child transmission of H. pylori was demonstrated in four out of five families, whilst transmission from father-to-child and sibling-to-sibling were demonstrated in two families and one family, respectively. Abbreviations: MLST, multi-locus sequence typing; RAPD, random amplification of polymorphic DNA; SNP, single nucleotide polymorphism.